Numbers for Successful Poultry Production - Gary D. Butcher; Amir H. Nilipour (EDIS)
Fertile egg production and incubation and production of broiler meat are both an art and a science. Man has taken full control of incubating fertile eggs by artificial means to supply the increasing world demand for poultry meat. It is estimated that worldwide more than 30 billion broiler fertile eggs are incubated annually. If eggs were still incubated naturally and broilers raised in small backyard farms, the poultry industry would not have been able to grow and prosper as it has and supply the world demand for poultry products. This document is VM133, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 10, 2002.